Coupling metal organic frameworks with molybdenum disulfide nanoflakes for targeted cancer theranostics. (18th January 2021) - Yang, Shuguang; Li, Dejian; Chen, Liang; Zhou, Xiaojun; Fu, Liwen; You, Yanling; You, Zhengwei; Kang, Li; Li, Maoquan; He, Chuanglong
Abstract : The construction of a multifunctional nanoplatform for the targeted delivery of antitumor drugs and photothermal therapy/chemotherapy of cancer. Abstract : The superior properties of metal organic frameworks (MOF) can provide great opportunities for merging functional nanoparticles to construct smart and versatile cancer theranostic agents. In this study, on the basis of non-mesoporous nanoparticles (molybdenum disulfide, MoS2 ), the structure of the MOF shell layer with an adjustable structure can be constructed through the natural coordination interaction between polydopamine (PDA) and iron ion, and the tumor cell target ligand was modified on the surface of the nanocomposite after loading the anticancer drug doxorubicin hydrochloride (DOX) to form a multifunctional cancer theranostics nanoplatform (DOX@MoS2 -PMA). Benefiting from the excellent properties of MoS2 and MOF, the favorable photothermal properties and pH/near-infrared (NIR) laser-triggered DOX release behavior of composite nanoparticles were demonstrated. Its well-defined nanostructure, adequate colloidal stability, and satisfactory biocompatibility were further evidenced. Furthermore, the selective tumor cell targeting ability of DOX@MoS2 -PMA can improve the cellular uptake efficacy and the photothermal-chemotherapy combination therapy can significantly enhance the killing effect on cancer cells both in vitro and in vivo . In addition, fluorescence imaging results show that nanoparticles can efficiently accumulate inside tumors. The photoacoustic (PA) and magnetic resonance (MR) imaging capabilities derived from different components of nanoparticles can perform better imaging effects. To the best of our knowledge, this is the first attempt to merge the performance of MoS2 with MOF for PA/MR dual-modality imaging-guided photothermal-chemotherapy combination therapy. Our work presented herein proves that MOF can be combined with non-mesoporous nanoparticles and exhibits excellent performance, thus opening a new avenue for endowing non-mesoporous nanoparticles with an efficient drug loading capacity and practical applications of MOFs in nanomedicine.